Job's diet : comfort, food and suffering / James K. Aitken. - Aitken, James K. (1968-2023)
Zakres i treść: the prose portion of Job, Job in the biblical tradition, the downfall of Job, comfort, physical conditions, ironic use of food, death as ravenous animal, conclusion, epilogue: a contemporary understanding.